Migration and Social History of Anjunadu: Lessons from the Past for Sustainable Development – An Applied Study - Santhosh George (PESQUISA, 2018)
At the north east portion of Idukki district of Kerala there are a few locations that shows extreme geographical differences compared to the rest of the district. These locations include places namely Marayoor, Kanthalloor, Keezhanthoor and Karayoor and Kottagudi - collectively known as the „Anjunadu‟ (Five places). We can experience a replication of Tamil culture on the valleys of this region. These gifted places are the abode of natural serenity, cluster of tribal settlements, a treasure of historical knowledge, a land of social formations and a can of cultural blending. Through this study the researcher tried to connect past and present for the future of the Anjunadus. Basic historical courses of this region are tried to be analyzed in order to prepare a comprehensive outline for the sustainable development of this region. Hence practicability has given more importance.